Pengaruh Penerapan media Interaktif Terhadap Kemampuan Kognitif Dalam Pembelajaran Permainan Bola Voli Siswa Kelas XI MA Diponegoro Bandung Tulungagung - murti, dhimas hari (Corner: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
Abstract The Covid-19 pandemic caused many changes, including in the field of education. This pandemic has disrupted learning from the beginning of learning activities carried out offline to online. Then media is needed for learning, and use interactive media based on Android applications. Like the research that has been done by researchers in applying interactive media to PJOK learning, especially volleyball games in teaching and learning activities. So this study aims to determine the effect of the application of interactive media in the cognitive domain of students. This type of research is a quantitative experiment. Methods of data collection using pre-test and post-test questions. The data collection instrument used a written test. The data analysis method uses the SPSS application version 25.0. The results showed that the experimental class (mean) pre-test 66.00 and post-test 78.33 for the control class obtained (mean) pre-test 64.00 and post-test 73.33, the normality of the p value is greater than the sig value .0.05(p>0.918), homogeneity test p(sig.) value of 0.46>0.05 and the results of the t test show the tcount value in this study is 12.854 with n = 15 while the ttable value for n = 15 with significance level α = 0.05 of 2.131 Thus the value of tcount = 12.854> ttable = 2.131, sig. value 0.00 <0.05. From this research, it is known that Ha is accepted, Ho is rejected, it is concluded that the application of interactive media increases students' cognitive abilities by 19.00%. So it can be concluded that PJOK learning is effective using interactive media.